Деякі задачі динамічного деформування трубопроводу на пошкодженій основі - Шацький, Іван; Васьковський, Максим (КІНПАТРІ ЛТД, 2013)
The dynamic problems on the stressed-strain state of pipeline under vibration, caused by cyclic motions of damaged body are considered.
Some problems for dynamic deformation of pipeline on damaged body